Expression and persistence of a lacZ reporter gene at various stages of tilapia (Oreochromis niloticus) - Alam, M D Samsul; Maclean, Norman (Indian Journal of Fisheries, 2011)
An Escherichia coli lacZ gene linked to the 4.6 kb carp -actin promoter/ enhancer was microinjected into the fertilised eggs of til apia COreochromis niloticus) at a concentration of 5xl05 copies per egg. The embryos grown from the injected eggs were homogenised at day 8 and day 14 after fertilization and half of the homogenate was used for assaying -galactosidase activity by a fluorometric method using 4-methyl-umbelliferyl D Galactoside as a substrate. DNA from the other half of the homogenate was analysed by Southern Blotting. The incidence of expression of the trans gene was 41.6 and 25.0% for the 8-days old embryo and 14 days old fry respectively. All the expressing individuals were positive for carrying the transgene in different concatemeric forms. Out of eight tissues analysed from a six-month old adult fish by X-Gal staining, only certain cells of the brain were found to be positive for express.on of the lacZ gene although the DNA was present in all the tissues when anal:sed by Southern Blotting.